1997
DOI: 10.1037/0033-2909.121.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Getting in: Criteria for acceptance of manuscripts in Psychological Bulletin, 1993–1996.

Abstract: They analyzed ratings provided by reviewers to determine what predictive value, if any, the ratings had for ultimate acceptance or rejection. The authors analyzed the weights of the various criteria through correlation and stepwise multiple-regression analysis. All ratings predicted final decisions, and these ratings were highly intercorrelated. The two strongest predictors were contribution to field reviewed and appropriateness of manuscript for journal. A common factor analysis suggested two factors underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Lack of originality [in this study an aspect considered in the area ''Relevance of contribution''] or inappropriate experimental design were likely to be associated with rejection. Conversely, aspects involving the presentation of manuscripts (tables, figures, references) were rarely cited as reasons to justify acceptance or rejection'' (p. 549, see also Abelson 1990;Sternberg et al 1997 The results of this study have various implications for authors, journal editors and referees (in the field of chemistry): The question for authors, following the rejection of their manuscript by a journal, is generally to which other journal the manuscript should be resubmitted. In the context of the results of this study, an author should then choose a journal for the resubmission with a similarly high reputation as that of the rejecting journal, if the criticism in the reviews does not relate to the relevance of the contribution, and the design/conception of the study is not fundamentally criticized, but rather if the criticism primarily relates to other areas.…”
Section: Discussionmentioning
confidence: 92%
“…Lack of originality [in this study an aspect considered in the area ''Relevance of contribution''] or inappropriate experimental design were likely to be associated with rejection. Conversely, aspects involving the presentation of manuscripts (tables, figures, references) were rarely cited as reasons to justify acceptance or rejection'' (p. 549, see also Abelson 1990;Sternberg et al 1997 The results of this study have various implications for authors, journal editors and referees (in the field of chemistry): The question for authors, following the rejection of their manuscript by a journal, is generally to which other journal the manuscript should be resubmitted. In the context of the results of this study, an author should then choose a journal for the resubmission with a similarly high reputation as that of the rejecting journal, if the criticism in the reviews does not relate to the relevance of the contribution, and the design/conception of the study is not fundamentally criticized, but rather if the criticism primarily relates to other areas.…”
Section: Discussionmentioning
confidence: 92%
“…Studies examining the relation of reviewer ratings of manuscript attributes to editors decisions have generally found that reviewers recommendations for publication are highly correlated with editors decisions (e.g., Bakanic, McPhail, & Simon, 1987;Fogg & Fiske, 1993;Lock, 1982;Sternberg, Hojjat, Brigockas, & Grigorenko, 1997;Zuckerman & Merton, 1971) and that reviewers ratings of manuscript attributes predict their own and editors publication judgments (Marsh & Ball, 1989;Sternberg et al, 1997). There is some question, however, about which manuscript attributes are most strongly associated with publication judgments.…”
Section: Queens Universitymentioning
confidence: 99%
“…In an experimental study, Wilson, DePaulo, Mook, and Klaaren (1993) found that fictitious studies that were about important topics were judged more likely to be published than identical studies which were about unimportant topics, even when the studies were fatally flawed methodologically. Studies within the review process itself have suggested that ratings of both importance and methodology are the most highly related to publication judgments, and in that order (Marsh & Ball, 1989;Sternberg et al, 1997).…”
Section: Queens Universitymentioning
confidence: 99%
See 2 more Smart Citations